Social Tourism for Youth Groups: Key Preferences and Trends - L. I. Donskova; A. L. Barannikov; M. U. Makovetsky (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The article studies youth tourism as a part of social tourism and a component of travelling system, which is characterized by social and economic features and impact by different factors and conditions. Theoretical and empiric research of youth tourism is topical, which is stipulated by such qualities of the younger generation as mobility, striving for cognition and today’s possibilities to organize leisure time and travelling. Due to complicated situation connected with COVID-19 and closing borders with foreign countries fast development of internal tourism is observed. The authors underlined specific features of youth tourism and showed its ties with territorial factors and conditions of future development. General academic methods, such as content-analysis, sociological method (survey was conducted among students of universities and colleges) and statistic methods: grouping, average-mean arithmetical ones were used in the research. While studying academic views of home and overseas scientists concerning youth tourism the authors paid attention to the importance of social and cultural components envisaged by travelling motivation for the given group of tourists and the impact of factors and conditions connected with regional features. It was pointed out that to plan the youth tourism development it is necessary to take into account preferences of young people in travel programs and events, various relations in social groups during holidays and travels, paying special attention on social and cultural components.